STRATEGI PRODUSER DALAM MEMERTAHANKAN PROGRAM SIARAN “JAPPA-JAPPA” DI SINJAI TV (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This thesis discusses "producer strategies in maintaining the Jappa-Jappa program on Sinjai Tv" by raising two substantive problems, namely: 1). What actions did the producers take to maintain the Jappa-Jappa program on Sinjai Tv? 2). What challenges do producers face in maintaining the Jappa-Jappa broadcast program on Sinjai Tv. This research aims to determine the actions taken by the Jappa-Jappa producer and the challenges faced in maintaining the Jappa-Jappa program on Sinjai TV. This type of research is qualitative research with a descriptive approach. The data sources for this research are primary data sources and secondary data. The data collection techniques used were observation, in-depth interviews, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion. The results of this research are, firstly, the producer of Jappa-Jappa first carried out careful planning before starting the production process, then determined the target audience so that this program was right on target, namely the general public, and used another strategy, namely narrowing down the target object by raising the theme Friendly Village. Second, the challenges or inhibiting factors in the Jappa-Jappa program production process are the lack of funding, lack of infrastructure, and limited human resources. This research implies that funding for the Jappa-Jappa program should be made sufficient so that the production process of this program is not hampered, Sinjai TV, especially producers, must procure adequate infrastructure such as cameras needed by the producer and team, for human resources that Sinjai lacks. TV must add members or employees so that each person works according to their respective duties and no longer needs to work on all existing programs.